(untitled) (Biological Sciences - PJSIR, 2018)
Laboratory studies were conducted to investigate the repellency effect of six plant species (Azadirachta indica, Caralluma fimbriata, Allium sativum, Curcuma longa, Citrullus colocynthis and Calotropis procera) against Sitophilus zeamais reared on maize grains (Cv. Azam White) in the Laboratory of Entomology Department, Gomal University, Dera Ismail Khan, Pakistan. Six concentrations viz. 5000, 10000, 15000, 20000, 25000 and 30000 ppm of each plant powder were applied to 20 g of sterilized maize grains under constant conditions of 27 ± 1°C and 65 ± 5% relative humidity. Twenty newly emerged adult maize weevil were introduced into glass petri dishes and percent repellency of plant powders was determined. A. indica seed powder at 30,000 concentration showed 100% repellency against maize weevil followed by C. longa (76%) after 72 h exposure period whereas C. procera was found least effective showing only 39% repellency of the test insects compared to control. The powders of A. sativum, C. fimbriata were found moderately repellent against the test insects. During the observations, it was also noted that repellency of the tested plant powders was dose dependent, the higher the concentration of the tested powders, the higher was the repellency and vice versa. The findings of this study indicated that the selected plant products could be used for a safer control of maize weevil.